Pengaruh Intensitas Modal, Leverage, Dan Ukuran Perusahaan Terhadap Agresivitas Pajak Dengan Profitabilitas Sebagai Variabel Moderasi Pada Perusahaan Manufaktur Sektor Industri Dasar dan Kimia Yang Terdaftar Di Bursa Efek Indonesia Periode 2019-2024 - Riyana Octaviani Lubis; Muhammad Arief (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
This research aims to determine the intensity of capital, leverage, and firm size on tax aggressiveness with profitability as a moderating variable in manufacturing companies in the basic and chemical industry sectors listed on the Indonesia Stock Exchange in 2019-2024. The sample selection method used is purposive sampling. The total observations in this research were 102 samples with 6 years of observation consisting of 17 companies. The data analysis technique used in this research is multiple linear regression analysis and moderation analysis. The results of the analysis in this research indicate that leverage and firm size affect tax aggressiveness, while capital intensity has no effect on tax aggressiveness. The results of moderation analysis show that profitability is able to moderate and strengthen the effect of leverage on tax aggressiveness, while profitability is not able to moderate and weaken the effect of capital intensity and firm size on tax aggressiveness.